Electrical Properties of CuO/PANI/Graphite Ternary Composites as a Potential Radar Absorbing Material - Dian Mart Shoodiqin; Fadli Robiandi; Agus Rifani (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
The development of lightweight, high-performance Radar Absorbing Materials (RAM) is critical for modern defense and telecommunication, yet traditional ferrite-based materials are often limited by high density and corrosion. This work investigates a novel ternary composite system as a lightweight solution, combining a high-permittivity CuO ceramic matrix with a dual-filler synergistic network of Polyaniline (PANI) and natural graphite. Composites with varying compositions were fabricated via mechanical mixing methods. The key finding is that a composite with 95% CuO, 2% PANI, and 2% Graphite (by mass) exhibited a DC electrical conductive of 0.38 S/m. This value represents a significant, 34-fold increase compared to a binary CuO/PA composite, confirming the formation of a synergistic percolation network at a very low (4%) total filler loading. This conductive falls directly within the optimal semi-conductive range required for balancing impedance matching and conductive attenuation. These results establish the CuO/PANI/Graphite ternary system as a highly promising candidate for developing efficient, lightweight radar absorbers.